Determinación de la calidad productiva de fincas de cacao Theobroma cacao) en sistemas agroforestales en la zona de Ricaurte, Ecuador. - Poma Ube, Jonathan Fabricio (2023)
The cultivation of cocoa (Theobroma cacao) in Ecuador is one of the main products with the highest demand, income, exports and jobs for thousands of families. The objective of this investigation was to evaluate the productive quality of cocoa farms in agroforestry systems in the Ricaurte area. The work area was in Ricaurte and to carry out this investigation, closed and open surveys were used as methodology, applied to 25 producers. of cacao, to guide the field work, reference was made to the sustainability assessment method in the Framework for the Assessment of Natural Resource Management Systems. (MESMIS) and General Sustainability Index (IGS), the general results show that 80% of the respondents have established the CCN-51 variety, 8% have a CCN -51 and twig mixture, and the remaining 12% others. materials, in addition, the owners surveyed 68% responded that they do not use associated systems on their farm and 32% responded that, if they maintain associated crops, indicating that few producers have trees associated with their crops, sustainability showed the best IGS values (>0.70) in only 8.00 % of the evaluated crops (Farms 11 and 19, figure 41.2), however, the increase in the index is mainly due to the indicator agricultural biodiversity and crop management, the other indicators expressed a normal behaviour.